Antimicrobial and Antioxidant Activities in 'Beluntas' (Pluchea indica), Turmeric (Curcuma longa) and Their Mixtures - Zabidi, Atiqah Ruqayyah; Ismail, Sayyidah Nafisah; Sempo, Muhammad Widus; Yahaya, Nazariyah; Mohd 'Azmi Mohd Razif (Univ Kebangsaan Malaysia, 2024)
Indexed by WOS